2017
DOI: 10.1111/jai.13354
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight relationships of 12 indigenous fish species in the Gajner Beel floodplain (NW Bangladesh)

Abstract: Summary The length–weight relationships (LWRs) were studied for 814 individuals covering eight families and 12 species of fish, e.g., Botia dario, Botia lohachata, Channa orientalis, Esomus danricus, Heteropneustes fossilis, Macrognathus pancalus, Nandus nandus, Ompok pabda, Pethia phutunio, Pethia ticto, Trichogaster fasciata and Trichogaster lalius captured from the Gajner beel floodplain, northwestern (NW) Bangladesh. Samples were collected occasionally from catches of fishermen from November 2014 to Octobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 12 publications
3
22
2
Order By: Relevance
“…The knowledge of life history traits of fish species is very significant to execution of proper management policies for protecting the economically important small fish like M. pancalus (Hossain et al, 2017). Studies of length frequency distributions (LFDs) usually express the ecology and life-history traits of fish (Khatun et al, 2019).…”
Section: Wetland Ecosystem Gajner Beelmentioning
confidence: 99%
See 1 more Smart Citation
“…The knowledge of life history traits of fish species is very significant to execution of proper management policies for protecting the economically important small fish like M. pancalus (Hossain et al, 2017). Studies of length frequency distributions (LFDs) usually express the ecology and life-history traits of fish (Khatun et al, 2019).…”
Section: Wetland Ecosystem Gajner Beelmentioning
confidence: 99%
“…Additionally, relative weight (W R ) is the most accepted index to recognize the pre-predator status of fishes in the worldwide since long time (Rypel and Richter, 2008) and now it is using in Bangladesh for assessing the pre-predator status of freshwater fishes (Hossain et al, 2013c;Rahman et al, 2019a,b). Hence, several authors reported on growth pattern (Hossain et al, 2006;Abujam and Biswas, 2016;Hossain et al, 2017;Islam et al, 2017: Karna et al, 2018, maturity and fecundity (Suresh et al, 2006;Pathok et al, 2012), truss morphometric studies (Mahfuj et al, 2019). Considering the economic importance of this species, no prior research on life history traits of M. pancalus from Bangladesh and elsewhere.…”
Section: Wetland Ecosystem Gajner Beelmentioning
confidence: 99%
“…Length–weight relationships (LWRs) are essential for studying fish stock assessment and population dynamics (Hossain, Hossen, Ahmed et al, 2017; Parvin et al 2018; Hossen, Rahman, Hossain et al, 2019), allowing calculation of weights consistent with a given body length. It is widely used in analyses of fishery data, mainly because of the difficulty and time required to record weights in the field (Andrade & Camos, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The LWRs have been widely used to assess stock biomass, age structure and function, dynamic and growth of fish populations (Asadi, Sattari, Motalebi, Zamani‐Faradonbeh, & Gheytasi, ; Özaydın, Uçkun, Akalın, Leblebici, & Tosunoğlu, ; Wang et al, ). Therefore, the LWRs are vital element in the research of fish physiology, taxonomy, ecology and fisheries management (Écoutin & Albaret, ; Hossain et al, ; Offem, Samsons, & Omoniyi, ; Wang et al, ). For instance, the LWRs are frequently applied to the life‐history traits analysis of different fish species or the same species from different localities (Hossain et al, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the LWRs are vital element in the research of fish physiology, taxonomy, ecology and fisheries management (Écoutin & Albaret, ; Hossain et al, ; Offem, Samsons, & Omoniyi, ; Wang et al, ). For instance, the LWRs are frequently applied to the life‐history traits analysis of different fish species or the same species from different localities (Hossain et al, ; Wang et al, ). In the field survey, LWRs can be used to convert length to weight and vice versa, especially when only length or weight measurements are available (Froese, ; Zeng, Huang, Chen, & Li, ).…”
Section: Introductionmentioning
confidence: 99%